Measurement of Radioactivity in Some Commercial Porcelain Samples by Using HPGe Detector - Ahmed, Firas Hashem; Mohammed, Ali N.; Karim, Mahmood Salim; Mansour, Hazim Louis (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Estimations of specific activity concentrations in eight commercial porcelain tiles made in different countries were performed by the use of HPGe detector. We have found that the highest specific activity concentrations for 238U, 40K were equal to (21.120 Bq/kg) and (283.862 Bq/kg) respectively, Iranian origin, while the highest specific activity concentration for 232Th was found to be equal to (29.292 Bq/kg), Iraqi origin; all of which were less than their corresponding recommended values given by (UNSCEAR, 2000). The radiation hazard indices [IÉ£ , Hin ,Hex , Raeq ,DÆ” , (AEDE) in and (AEDE) out] were also studied and their values were less than the allowed values determined by (UNSCEAR, 2000). Therefore, all the studied tiles of commercial porcelain are safe when used, for example, in floor constructions.